Topical instillation of cell-penetrating peptide-conjugated melphalan blocks metastases of retinoblastoma. (May 2022) - Jiang, Kuan; Fan, Xingyan; Hu, Yang; Yao, Shengyu; Liu, Yu; Zhan, Changyou; Lu, Weiyue; Wei, Gang
Abstract: Retinoblastoma is the most common primary intraocular malignancy in infancy with a metastases-related death risk. However, a safe and convenient treatment without enucleation is still an unmet clinical need. In this work, a cell-penetrating peptide, 89WP, was conjugated with melphalan (89WP-Mel), which achieved high tumor inhibition effects as intravitreally injected melphalan via topical instillation for the first time. Notably, the "outside-in" diffusion of instilled 89WP-Mel created a protective shield surrounding the eye, efficiently preventing tumor metastases, while the mice treated with intravitreally injected melphalan suffered more brain metastases related death. The ocular absorption of 89WP-conjugated melphalan and other small molecules, both hydrophobic and hydrophilic, occurred via non-corneal pathway with high safety and a prolonged residence duration in retina up to 24 h. The present work paves a new avenue for simultaneous intraocular tumor inhibition and extraocular metastases prevention in a safe and convenient way via topical instillation.